Hubungan Fasilitas dengan Tingkat Kepuasan Pelayanan Keperawatan di Ruang Rawat Inap RSUD Dr. A. Dadi Tjokrodipo Bandar Lampung - Ria Mualifah; Aryanti Wardiyah; M. Ricko Gunawan (Universitas Malahayati Lampung, 2024)
ABSTRACT Preliminary data from 15 patients found that 10 respondents (66.7%) were dissatisfied with the availability of service facilities at RSUD Dr. A. Dadi Tjokrodipo, the patient said that if the nurse performed the infusion change and release the infusion without carrying a tray, the nurse would only bring a bowl and a container of alcohol cotton. In addition, patients also complain of hard patient beds, uncomfortable linens/sheets. Then 5 other respondents (33.3%) were satisfied with the facilities provided by the Hospital, including the availability of clean bathrooms, the availability of litter boxes, good ventilation and lighting. To determine the relationship between the facility and the level of patient satisfaction in the inpatient room of RSUD Dr. A. Dadi Tjokrodipo Bandar Lampung. This type of research uses quantitative, the research design uses a survey with a cross sectional approach. P The population in this study were clients who were hospitalized in Room E4 RSUD DR. A. Dadi Tjokrodipo Bandar Lampung City in November as many as 320 respondents. The sampling technique uses purposive sampling. Univariate and bivariate data analysis The sample in this study used the slovin formula so that a sample of 178 respondents was obtained. This research was conducted in July 2023. Data analysis used the univariate and bivariate tests using the chi square test. Most of the respondents stated that the facilities were in the good category, 91 respondents (51.1%). Most of the respondents stated patient satisfaction in the satisfied category as many as 100 respondents (56.2%). The results of data analysis using the chi square test obtained a p-value = 0.000 (α 0.05), which means that there is a relationship between facilities and the level of patient satisfaction in the inpatient room of RSUD Dr. A. Dadi Tjokrodipo Bandar Lampung. It is also hoped that medical personnel and paramedics need to provide appropriate services according to establi Keywords: Facilities, Satisfaction Level, Patients ABSTRAK Data pendahuluan dari 15 pasien ditemukan 10 responden (66,7%) memiliki rasa kurang puas dengan ketersediaan fasilitas pelayanan di RSUD Dr. A. Dadi Tjokrodipo, pasien menyebutkan jika perawat melakukan tindakan penggantian infus dan pelepasan infus tanpa membawa baki, perawat hanya membawa bengkok dan wadah kom kapas alkohol. Selain itu pasien juga mengeluhkan bed pasien yang keras, laken/ sprei yang tidak nyaman. Kemudian 5 responden lainnya (33,3%) memiliki rasa puas dengan fasilitas yang diberikan oleh Rumah Sakit, meliputi tersedianya kamar mandi yang bersih, tersedianya kotak sampah, ventilasi dan pencahayaan yang baik. Untuk mengetahui hubungan fasilitas dengan tingkat kepuasan pasien di ruang rawat inap RSUD Dr. A. Dadi Tjokrodipo Bandar Lampung. Jenis penelitian menggunakan kuantitatif, rancangan penelitian menggunakan survey dengan pendekatan cross sectional. P Populasi dalam penelitian ini adalah klien yang melakukan rawat inap di Ruang E4 RSUD DR. A. Dadi Tjokrodipo Kota Bandar Lampung pada bulan November sebanyak 320 responden. Teknik sampling menggunakan purposive sampling. Analisa data univariat dan bivariat Sampel dalam penelitian ini menggunakan rumus slovin sehingga didapat sampel 178 responden. Penelitian ini dilakukan pada bulan Juli tahun 2023. Analisa data menggunakan uji univariate dan bivariate menggunakan uji chi square. Sebagian besar responden menyatakan fasilitas dengan kategori baik sebanyak 91 responden (51,1%). Sebagian besar responden menyatakan kepuasan pasien dengan kategori puas sebanyak 100 responden (56,2%). Hasil analisa data menggunakan uji chi square didapat nilai p-value = 0.000 ( α 0,05) yang artinya ada hubungan fasilitas dengan tingkat kepuasan pasien di ruang rawat inap RSUD Dr. A. Dadi Tjokrodipo Bandar Lampung. Diharapkan pula, bagi tenaga medis dan para medis perlu memberikan pelayanan yang tepat sesuai prosedur yang ditetapkan seperti memberikan perhatian kepada setiap pasiennya dan memberi informasi kesehatan yang jelas kepada pasien. Kata Kunci: Fasilitas, Tingkat Kepuasan, Pasien